Pengaruh Pemberian Probiotik Delacto Sistem Bioflok dengan Dosis yang Berbeda Pada Pakan Buatan terhadap Pertumbuhan Berat Mutlak Ikan Nila (Oreochromis niloticus) - Antoni Tri Mahendra; Didik Budiyanto; Sri Oetami Madyowati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The use of probiotics is very important in cultivation activities. Probiotics are live microorganisms that have a beneficial effect on the host by balancing the microflora in their intestines. In increasing the nutritional content of artificial feed (pellets), the bacteria in probiotics have a mechanism for forming several enzymes for digesting feed. This study aims to determine the effect of giving delacto probiotics at different doses in artificial feed on the absolute weight growth of tilapia (Oreochromis niloticus). Probiotics are mixed with feed using a biofloc cultivation system. The method used in this research was an experimental method with a Completely Randomized Design (CRD) with 4 treatments and 6 replications, namely by adding different doses to the treatments. Treatments A (8ml/kg), B (16 ml/kg), C (24 ml/kg) and D (32 ml/kg). The parameter observed was absolute weight growth. Water quality supporting parameters include temperature, pH and DO. Data were analyzed using the ANOVA test. Based on the research results, it shows that giving different doses of delacto probiotics has a significant effect on the absolute weight growth of tilapia (Oreochromis niloticus). Treatment A (8 ml/kg) gave the lowest absolute weight growth of 32.83 grams and treatment D (32 ml/kg) gave the highest absolute weight growth of 40.57 grams. Water quality parameters include water temperature ranging from 25.3 – 26.1֯C, acidity ranging from 7.5 – 8.0. And dissolved oxygen ranges from 4.7 – 5.3 ppm. The results of analysis of variance (ANOVA) for the three water quality parameters showed no differences between treatments (Oreochromis niloticus) fry.